Analisis Karakteristik Hakikat Pembelajaran IPA di Sekolah Dasar - Dewi Tila Elisa; Mikael Bumbun; Pebria Dheni Purnasari; J Juliana; B Bundel; S Silvester (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2023)
Education in Indonesia is currently demanded to be even better about what students have received. The researcher made this article to provide a new idea related to learning natural sciences in general. This type of research is qualitative research with a descriptive model. On this occasion, the researcher only got a number of learning models that can be described based on the results of observations that have been made, namely the lecture learning model by providing material orally and in practice, but only in the environment around the school. Through the results of the observations that have been made, it can be seen that science learning is real or factual learning about the universe and everything in it.